Clinicians' perceptions of delivering new models of high intensity aphasia treatment. Issue 4 (3rd April 2017) - Gunning, Dana; Wenke, Rachel; Ward, Elizabeth C.; Chalk, Shannon; Lawrie, Melissa; Romano, Michelle; Edwards, Ann; Hobson, Tania; Cardell, Elizabeth
ABSTRACT: Background: While evidence suggests that intensive aphasia therapy is associated with positive patient outcomes, speech language pathologists continue to report delivering therapy at low intensity schedules. Investigation of the barriers and enablers of delivering intensive therapy in hospital settings is needed to help address this evidence–practice gap. Aims: To explore clinicians' perceptions of delivering high intensity aphasia treatment through three different service models and their recommendations for future directions in implementing high intensity aphasia clinics in a public health setting. Methods & Procedures: A sequential mixed methods design was employed. Thirteen speech language pathologists who provided intensive aphasia therapy to 31 patients across three facilities as part of a larger study consented to participate. Participants contributed to a log of barriers and facilitators while delivering treatment and completed a questionnaire in the last week of treatment. Findings were used to inform the question guide for a focus group interview conducted with nine of the clinicians post-treatment. Outcomes & Results: Most clinicians found the increased intensity of treatment more difficult to deliver than standard treatment, and reported barriers included patient fatigue, patient personal factors, locating resources, scheduling and coordination issues, and clinician workload and potential burn-out. Emotional challenges were less expected and were potentially intensified by the frequency of contact with patients. Despite this, clinicians remained dedicated, and were motivated by patient progress, peer support and the opportunity to prove the worth of speech language pathology. They were positive about the perceived benefits of patient confidence, clinician development, teamwork, and the relationships that formed between patients, carers and clinicians. Conclusions: Clinicians agreed that delivering the treatment brought great rewards and benefits, but also challenges. Communicating the benefits and finding ways to address the barriers identified by the participants of this study may be instrumental in assisting future implementation of high intensity models of aphasia treatment in existing services.